ANALISIS KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH DALAM MENINGKATKAN KOMPETENSI GURU DI SD NEGERI 548 RANTE ALANG KECAMATAN LAROMPONG KABUPATEN LUWU - Hartadinata Akib; Ilyas; Muhammad Hasbi Abbas (STKIP Subang, 2026)
Teacher competence is one of the key determinants of educational quality. However, improving teacher competence requires effective school leadership that is capable of motivating, guiding, and empowering teachers to develop professionally. This study aimed to analyze the transformational leadership of the principal in improving teacher competence at SD Negeri 548 Rante Alang, Larompong District, Luwu Regency. The study employed a descriptive qualitative approach. Data were collected through interviews, observations, and documentation involving the principal, teachers, school supervisors, and the school committee. Data were analyzed using the interactive model of Miles, Huberman, and Saldana, which consisted of data reduction, data display, and conclusion drawing. The findings revealed that the principal implemented transformational leadership through four dimensions, namely idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. The implementation of these dimensions contributed to the improvement of teachers’ pedagogical, professional, social, and personal competencies. Supporting factors included teachers’ commitment to professional development, positive collaboration among school stakeholders, support from school supervisors, and participation in Teacher Working Groups (KKG). Meanwhile, limited facilities and differences in teachers’ abilities to adapt to educational developments were identified as inhibiting factors. The study concludes that transformational leadership plays a significant role in improving teacher competence and supporting the enhancement of educational quality in elementary schools.